Altered Expression of NF-κB and SP1 after Exposure to Advanced Glycation End-Products and Effects of Neurotrophic Factors in AGEs Exposed Rat Retinas - Guzel Bikbova; Toshiyuki Oshitari; Takayuki Baba; Shuichi Yamamoto (Journal of Diabetes Research)
To determine the effect of advanced glycation end-products (AGEs) on neurite regeneration, and also to determine the regenerative effects of different neurotrophic factors (NTFs) on rat retinal explants, the retinas of SD rats were cultured in three-dimensional collagen gels and incubated in 6 types of media: (1) serum-free control culture media; (2) 100 μg/mL AGEs-BSA media; (3) AGEs-BSA + 100 ng/mL neurotrophin-4 (NT-4) media; (4) AGEs-BSA + 100 ng/mL hepatocyte growth factor media; (5) AGEs-BSA + 100 ng/mL glial cell line-derived neurotrophic factor media; or (6) AGEs-BSA + 100 µM tauroursodeoxycholic acid media. After 7 days, the number of regenerating neurites was counted. The explants were immunostained for nuclear factor-κB (NF-κB) and specificity protein 1 (SP1). Statistical analyses were performed by one-way ANOVA. In retinas incubated with AGEs, the numbers of neurites were fewer than in control. All of the NTFs increased the number of neurites, and the increase was more significant in the NT-4 group. The number of NF-κB and SP1 immunopositive cells was higher in retinas exposed to AGEs than in control. All of the NTFs decreased the number of NF-κB immunopositive cells but did not significantly affect SP1 expression. These results demonstrate the potential of the NTFs as axoprotectants in AGEs exposed retinal neurons.